Interpenetrating polymer networks derived from silylated soybean oil and polydimethylsiloxane. Issue 4 (27th May 2013) - Dewasthale, Sudhanwa; Shi, Xiangke; Hablot, Elodie; Graiver, Daniel; Narayan, Ramani
ABSTRACT A series of interpenetrating polymer networks (IPNs) was prepared using various concentrations of silylated soybean oil and polydimethylsiloxane (PDMS) that were cross linked with inorganic silicates. This series of IPNs was prepared from emulsions of silylated soybean oil and PDMS together with colloidal silica and dioctyltin dilaurate catalyst at pH 10. Under these conditions, water soluble silicates reacted with silanols in the oil phase and formed intraparticle siloxane cross links. Upon casting films and evaporation of the water, additional interparticle cross linking were obtained between the coagulating particles to produce entangled networks of soybean oil and PDMS that were further reinforced by fine silica particles. The morphology revealed intimate mixing of the two immiscible components. The mechanical properties depended on the ratio of the soft, flexible PDMS phase and the rigid, brittle cross linked silylated soybean oil phase. These IPNs can be used as high release liners, low friction materials, or as a general protective coating. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 2479–2486, 2013